Case report: Myocardial perfusion gated-SPECT in pulmonary artery hypertension—the Movahed's sign - Hamzaraj, Kevin; Angjeliu, Silvia; Knopf, Paul; Stadler, Michael; Zbucki, Kamil; Kastrati, Lisbona; Graf, Senta; Gyöngyösi, Mariann; Hacker, Marcus; Calabretta, Raffaella (Frontiers in Cardiovascular Medicine, 2023)
Primary pulmonary artery hypertension (PAH) is a clinical diagnosis that requires the exclusion of other underlying causes of pulmonary hypertension (PH). Increased pulmonary artery (PA) pressure and subsequent right ventricular (RV) pressure overload often result in a flattening of the curved interventricular septum, leading to a D-shaped left ventricle (LV), as observed in echocardiographic short-axis views. A similar finding may be also observed on myocardial perfusion SPECT images, the so-called Movahed's sign. We present a clinical case of a female patient with PAH and progression of exertional dyspnea that underwent myocardial perfusion SPECT to investigate LV myocardial ischemia. The SPECT images revealed enhanced tracer uptake in the dilated right ventricle. Additionally, we observed a D-shaped LV or Movahed's sign, which may serve as a potential marker of RV pressure overload, along with a small stress-induced perfusion defect on the LV septal wall. Our findings highlight the importance of considering the presence of a D-shaped LV and signs of RV pressure overload, as they can alter the interpretation of LV perfusion deficits on SPECT images. This case report aims to emphasize the complex nature of right heart abnormalities in pathologies such as PAH and the consideration of the RV implications in myocardial SPECT images—which typically focus solely on the LV.